Cloud scale ISM structure and star formation in M51 - Leroy, Adam K.; Kruijssen, Diederik; Bigiel, Frank; Chevance, Mélanie (Arxiv, 2017)
We compare the structure of molecular gas at $40$ pc resolution to the ability of gas to form stars across the disk of the spiral galaxy M51. We break the PAWS survey into $370$ pc and $1.1$ kpc resolution elements, and within each we estimate the molecular gas depletion time ($τ_{\rm Dep}^{\rm mol}$), the star formation efficiency per free fall time ($ε_{\rm ff}$), and the mass-weighted cloud-scale (40 pc) properties of the molecular gas: surface density, $Σ$, line width, $σ$, and
Gesehen am 18.10.2017